2008
DOI: 10.1590/s0100-204x2008001100017
|View full text |Cite
|
Sign up to set email alerts
|

Fertilidade do solo, nutrição mineral e produtividade da bananeira irrigada por dez anos

Abstract: Resumo -O objetivo deste trabalho foi avaliar as alterações na fertilidade do solo, na nutrição mineral e na produtividade de bananeira irrigada por dez anos. O experimento foi conduzido em Latossolo Vermelho eutrófico, de 1997 a 2007, no Município de Janaúba, MG, em um plantio comercial de banana 'Prata-Anã', onde se utilizam, para irrigação por gotejamento, água calcária de poço tubular com salinidade alta e concentração média de sódio. Observou-se que a aplicação da irrigação, por dez anos, promove forte el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
5
1
7
Order By: Relevance
“…In terms of productivity, our values were higher than those found by Fernandes et al (2008), who evaluated the yield of the banana cultivar 'Prata Anã' irrigated with a drip system, with two lateral lines per plant row over a period of 10 years, and obtained an average productivity of 18.2 Mg ha -1 . However, our values are comparable with those of Nunes et al (2008), who reported that banana yields under conventional, highly technological, fertilizer-intensive, and systematic pest and disease control conditions can exceed 30 Mg ha -1 .…”
Section: Resultscontrasting
confidence: 79%
“…In terms of productivity, our values were higher than those found by Fernandes et al (2008), who evaluated the yield of the banana cultivar 'Prata Anã' irrigated with a drip system, with two lateral lines per plant row over a period of 10 years, and obtained an average productivity of 18.2 Mg ha -1 . However, our values are comparable with those of Nunes et al (2008), who reported that banana yields under conventional, highly technological, fertilizer-intensive, and systematic pest and disease control conditions can exceed 30 Mg ha -1 .…”
Section: Resultscontrasting
confidence: 79%
“…This tendency was presented by Fernandes et al (2008), who observed quadratic behavior in the production of 'Prata Anã' banana, with maximum point in the sixth year of cultivation. Oliveira et al (2008) also observed, among thirteen banana cultivars, including 'Prata Anã' , that the yield in the 3 rd cycle was higher than in the 2 nd cycle.…”
Section: Resultsmentioning
confidence: 76%
“…Fernandes et al (2008) avaliaram a 'Prata-Anã', irrigada por gotejamento, com uso de água calcária de poço tubular com salinidade alta e concentração média de sódio, durante dez anos. Embora também classificada como C 3 S 1 , a água utilizada era de pior qualidade em comparação à do presente trabalho.…”
Section: Resultsunclassified